2019
DOI: 10.1002/jnr.24574
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GluN2C in cerebral ischemia: GluN2C expressed in different cell types plays different role in ischemic damage

Abstract: Over the past decade, many studies have focused on clarifying the roles of different N-methyl-d-aspartate (NMDA) receptor subunits in cerebral ischemia, hoping to develop subunit-selective drugs. Recently, more attention was given to studying the role of GluN2C in ischemia damage, which may lead to the development of new NMDA receptor antagonists for cerebral ischemia. Results showed that GluN2C inhibition or knockout can effectively alleviate the ischemic injury caused by middle cerebral artery occlusion and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 72 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Among NMDA receptor subunits, GluN2C is characterized with low sensitivity to magnesium block, low conductance, low calcium permeability and low opening probability. It was reported that neuronal GluN2C confer protective effects, whereas oligodendrocytic and astrocytic GluN2C mediates detrimental effects (reviewed in Ding et al, 2020). Therefore, the high expression of GRIN2C in the neuronal subcluster UnN3 might mediate protective effects.…”
Section: Integrated Sc/snrna-seq Dataset Offers Insights Into Parkins...mentioning
confidence: 99%
“…Among NMDA receptor subunits, GluN2C is characterized with low sensitivity to magnesium block, low conductance, low calcium permeability and low opening probability. It was reported that neuronal GluN2C confer protective effects, whereas oligodendrocytic and astrocytic GluN2C mediates detrimental effects (reviewed in Ding et al, 2020). Therefore, the high expression of GRIN2C in the neuronal subcluster UnN3 might mediate protective effects.…”
Section: Integrated Sc/snrna-seq Dataset Offers Insights Into Parkins...mentioning
confidence: 99%